Pelaksanaan Pembelajaran Pendidikan Agama Islam di SMPN 2 Padang Ganting Kabupaten Tanah Datar - Syafrin, Yulia; Kamal, Muhiddinur; Arifmiboy, Arifmiboy; Husni, Arman (Indonesian Research Journal on Education, 2023)
Based on the initial observations that the writer made at SMP N 2 Padang Ganting, especially in class VII I, the writer saw that the students were less enthusiastic about learning this where it was seen that many students were noisy and talking with their friends and some students came in and out of class when the teacher was explaining the lesson. so that the learning process that the author sees is less effective. In addition, the learning outcomes are also unsatisfactory, where students do not understand the material presented by the teacher, the authors assume that some students still get low scores when the teacher carries out the assessment process onPAI subjects. This research is field research (field research) which is descriptive qualitative. In collecting data, the authors conducted observations, interviews, and documentation. The informants in this study were PAI teachers and class VII I students of SMP N 2 Padang Ganting. After the data was collected, the authors processed it using descriptive analysis. From the results of the research that the authors conducted, it can be concluded that in the implementation of PAI learning in class VII I at SMP N 2 Padang Ganting school, various methods are used because learning PAI has different characteristics. Among the methods used are thelecture method, the question and answer method, and the recitation method (assignments), while other methods such as the discussion method, the drill method (practice), the group work method, the demonstration method, the problem-solving method, the experimental method are very rare. used by teachers. Meanwhile, the media used by the teacher is picture media and sometimes used in focus and using blackboards, textbooks, andworksheets in the learning process. Meanwhile, film and music media were never used by teachers in PAI learning. So by using a variety of methods by PAI teachers in class VII I at SMP N 2 Padang Ganting, students have started to focus their attention on learning.